A bibliometric and visualization analysis of entosis research from 2007 to 2024 - Yang, Xinyu; Tu, Jiatao; Zang, Xinyi; Huang, Xuan (Frontiers in Oncology, 2024)
ObjectiveIn 2007, entosis was proposed as a form of programmed cell death, distinct from apoptosis. This process involves a living cell (internalized cell) actively invading a neighboring live cell of the same type (host cell), forming a cell-in-cell structure. Recently, entosis has been increasingly associated with cancer, leading to significant advancements in research. Despite this progress, a comprehensive and unbiased review of the current state of entosis research is lacking. This study aims to evaluate the developments in the field of entosis over the past decade and highlight emerging research trends.Materials and methodsWe performed a literature search for studies published since the introduction of the entosis concept, using the Web of Science Core Collection database. The bibliometric analysis was conducted using VOSviewer, CiteSpace, Microsoft Excel, and the Bibliometrix R package.ResultsA total of 196 articles from 39 countries and 346 institutions were included. Between 2007 and 2024, research on entosis has seen rapid growth, with most publications originating from China and the United States. The United States also leads in total citations, with Memorial Sloan Kettering Cancer Center emerging as the top research institution. Sun Qiang is the most prolific author in this field, while Overholtzer M has the highest number of citations. Current Molecular Medicine has published the most articles related to entosis. Frequently occurring keywords include “entosis,” “cannibalism,” “autophagy,” and “apoptosis.” In recent years, keywords such as “phagocytosis,” “drug resistance,” and “human cancers” have surged, indicating a growing focus on understanding the role of entosis in tumor progression and exploring its potential as a therapeutic target for cancer treatment.ConclusionsThis study provides the first bibliometric analysis of entosis, detailing its evolution over the last decade. It highlights critical areas of interest, including the development of inhibitors targeting entosis and their potential clinical applications. This research aims to guide future investigations and serve as a valuable resource for scholars exploring entosis in cancer biology.